Citra Merek, Kualitas Produk, Persepsi Harga, dan Promosi terhadap Keputusan Pembelian - Cahya Abim Maulana; Ali Maskur (Journal of Management and Bussines (JOMB), 2023)
This study aims to analyze the influence of brand image, product quality, price perception, promotion on the purchase decision of Xiaomi smartphones in the city of Semarang. This research method is descriptive qualitative by obtaining primary data obtained directly from the source by using a questionnaire. The population of this study is consumers who have made purchasing decisions for Xiaomi smartphones in the city of Semarang. In this research using a purposive sampling method with a sample used in this study as many as 100 respondents. Data analysis used validity test, reliability test, multiple linear regression analysis test, F test, coefficient of determination test (RÂ²) and t test (hypothesis), then by testing the data in this study using SPSS version 22. The results showed, a) the brand image variable is obtained from the regression coefficient (beta) of 0.297 with a significant level of 0.04 which means less than 0.05; b) the product quality variable is obtained from the regression coefficient (beta) of 0.255 with a significant level of 0.01 which means less than 0.05; c) the price perception variable is obtained from the regression coefficient (beta) of 0.283 with a significant level of 0.02 which means less than 0.05. In conclusion, brand image, product quality, price perception, and promotion found that these variables have apositive and significant effect on the decision to purchase a Xiaomi smartphone in the city of Semarang. Keywords: Brand Image, Product Quality, Perceived Price, Promotion